Successful Treatment of Scalp Myxedema with Injected Hyaluronidase: A Case Report - Menzinger, Sébastien (Dermatopathology (Basel), 2020)
Localized myxedema is an uncommon complication of Graves' disease. It is characterized by the accumulation of glycosaminoglycans, particularly hyaluronate. Here we describe the case of a 51-year-old female patient suffering from Graves' disease, who has presented for years a thickening of the scalp, consistent with myxedema, and successfully treated with repeated injections of hyaluronidase.